Analisis Hubungan Emotional Brand Attachment Dengan Consumer Based Brand Equity pada Industri Fashion Lokal: (Studi Kasus Pada Brand 3second) - Zembar Rizki, Ardalepa (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of Emotional Brand Attachment on customer-based brand equity through the mediating role of brand credibility and customer satisfaction on the 3Second brand in Sukabumi City. The method used is a quantitative approach with Structural Equation Modeling (SEM) analysis techniques to test the relationship between variables. The sample in this study consisted of 128 respondents who are 3Second brand users, determined through a purposive sampling technique. The results show that Emotional Brand Attachment has a significant effect on brand credibility and customer satisfaction . However, Emotional Brand Attachment does not have a direct effect on customer-based brand equity, but rather through customer satisfaction as a mediator. On the other hand, brand credibility does not have a significant effect on customer-based brand equity. These findings confirm that customer satisfaction plays a crucial role in forming strong brand equity. Therefore, companies need to pay attention to the overall consumer experience to increase loyalty and positive perceptions of the brand. This study contributes to the development of consumer-based marketing theory and serves as a practical reference for brand strategy management in the local fashion industry.